Antiretroviral therapy: Racial disparities among publicly insured Californians with HIV - LANDOVITZ, RAPHAEL J. (J Health Care Poor Underserved, 2017)
Only 43% of Americans with HIV are virally suppressed; the rate is lower for African Americans, even among insured populations. This study uses 2010 Medicare and Medicaid data for HIV-positive Californians to examine how antiretroviral treatment (ART) relates to patient and provider characteristics. Logistic regressions isolated the effect of race/ethnicity on receipt of ART. Over 90% of the full sample received any ART. Nearly 80% of ART users received a recommended combination for at least half the year; half had a recommended combination for 90% of the year. Lacking evaluation and management visits, or seeing only providers with low HIV patient volume lowered the odds of receiving ART. Controlling for other factors, African Americans remained less likely to receive ART at all, or to be covered for 90% of the year with a recommended regimen. The observed racial treatment differentials may lead to important health disparities.